2019
DOI: 10.2147/cmar.s188926
|View full text |Cite
|
Sign up to set email alerts
|

<p>Morbidity and associated factors of depressive disorder in patients with lung cancer</p>

Abstract: Objective The aim of this study was to assess morbidity and associated factors in patients with lung cancer (LC). Methods This study used a cross-sectional design with consecutive sampling. Study subjects were recruited from the LC outpatient clinic and inpatient ward in a medical center from March 2016 to February 2018. Patients with LC were enrolled and assessed using the Mini International Neuropsychiatric Interview, Hamilton Depression Rating Scale, Hamilton Anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 63 publications
5
19
0
2
Order By: Relevance
“…This finding was in line with that of our previous study, in which anxiety severity was an associated factor of depressive disorder in people with lung cancer. 34 Anxiety commonly co-occurs with depressive disorder, and the comorbidity of anxiety and depression in caregivers of persons with PD warrants clinical concern. Prior studies have shown that fatigue is associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in line with that of our previous study, in which anxiety severity was an associated factor of depressive disorder in people with lung cancer. 34 Anxiety commonly co-occurs with depressive disorder, and the comorbidity of anxiety and depression in caregivers of persons with PD warrants clinical concern. Prior studies have shown that fatigue is associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of patients with cancer suffer pain, and indeed, pain is an important issue in cancer management. In a study including 104 lung cancer patients, Lee et al reported 50% of patients had a psychiatric diagnosis and the most prevalent psychiatric disorder was depressive disorder (25.0%) (34). American Psychiatric Association (APA) published 'Diagnostic and Statistical Manual of Mental Disorders'…”
Section: Discussionmentioning
confidence: 99%
“…Trầm cảm có thể làm tăng các triệu chứng cơ thể, giảm tuân thủ điều trị ung thư và tăng tỷ lệ tự sát. Nghiên cứu đã chứng minh rằng triệu chứng trầm cảm làm giảm chất lượng cuộc sống của bệnh nhân ung thư và tăng tỷ lệ tử vong từ 25-39% [4], [5].…”
Section: đặT Vấn đềunclassified